(untitled) (Journal Of Educational and Psychological Researches, 2011)
This research aims at identifying problems that the Iraqi widow woman suffers from. The research is limited to a Sample of terrorism victims widows which is up to (70) widows from Al-Amal center for widows and orphans care in Baghdad. Results: Results show that: (Society inferior view) is ranked at the first stage of importance (Money impoverishment and economic dependency to others is ranked at the second stage of importance. (Sense of helplessness and weakness) is ranked at the third stage of importance. (Bad care from husbands parents) is ranked at the fourth stage of importance (feeling of psychological and emotional of vacuum) is ranked at the fifth stage of importance.(the interference of husbands parents in matters that pertain to the wife’s life)is ranked at the sixth stage of importance. (Feeling that life is tasteless is ranked at the seventh stage of importance. (Fear from harm that may effect the Sons)is ranked at the eighth stage of importance. (Feeling of the psychological isolation) is ranked at the ninth stage of importance) (Feeling of insecurity) is ranked at the tenth stage of importance. While other items are ranked from 11-23 of importance. Recommendation: • Its necessary to let this huge class of people go out from their houses and support them financially by lending then loans or small amount of grants to make jobs. • Provide media with programs directed to this class of people, as well as enhancing self- confidence to let them feel ambitions and that the future is bright with open doors.